Pengaruh metode Short Messaging Service (SMS) terhadap kepatuhan menelan Obat Anti-TB - Susan Susyanti; Hanna Rizmadewi Agustina (STIKes Karsa Husada Garut, 2014)
One factor that plays an important role for the treatment of tuberculosis (TB) is TB patient adherence factor itself. TB recurrence rates showing an increase of about 2.5 times that indicate a problem both from a medical aspect, immunological and psychological patients. SMS method is one of the alternative methods that can be used to remind patients with TB disease of anti-tuberculosis drugs ingest on a regular basis. The purpose of this review is to describe a variety of nursing and or health literature that discussed the cellular-based communication using SMS in patients with TB in improving adherence to swallow anti-tuberculosis drugs, and then to critically evaluate the evidence available to support nursing practice of the community, especially related to health promotion. Data collected in the form of journal literature published research, traced using EBSCOhost-CINAHL, ProQuest, PubMed, HealthMed Journal, etc. by using the key word